2014
DOI: 10.1021/ac501393a
|View full text |Cite
|
Sign up to set email alerts
|

2-Pyridylfuran: A New Fluorescent Tag for the Analysis of Carbohydrates

Abstract: We herein report the use of 1,3-di(2-pyridyl)-1,3-propanedione (DPPD) as a fluorogenic labeling reagent for sugars. Reaction of DPPD with the anomeric carbon affords a fluorescent 2-pyridylfuran (2-PF) moiety that permits the sensitive HPLC-based detection of monosaccharides. 2-PF-labeled monosaccharides can be easily separated and analyzed from mixtures thereof, and the reported protocol compares favorably with established labeling reagents such as 2-aminobenzoic acid (2-AA) and 1-phenyl-3-methyl-5-pyrazolone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…A fluorescent pyridylfuran moiety was formed upon incubation of saccharide and 1,3-di(2-pyridyl)-1,3-propanedione overnight at 110 °C. D-Galactose pyridylfuran derivatives can be detected at femtomole levels, which are significantly lower than traditionally used fluorescent tags 108 . Such tags also permit faster separations, where monosaccharide derivatives can be resolved within 6 minutes with liquid chromatography.…”
Section: Sample Preparation and Derivatizationmentioning
confidence: 77%
“…A fluorescent pyridylfuran moiety was formed upon incubation of saccharide and 1,3-di(2-pyridyl)-1,3-propanedione overnight at 110 °C. D-Galactose pyridylfuran derivatives can be detected at femtomole levels, which are significantly lower than traditionally used fluorescent tags 108 . Such tags also permit faster separations, where monosaccharide derivatives can be resolved within 6 minutes with liquid chromatography.…”
Section: Sample Preparation and Derivatizationmentioning
confidence: 77%
“…In yet another novel strategy, monosaccharides were labeled with the fluorescent tag, 2-pyridylfuran (2-PF), introduced by reaction with 1,3-di(2-pyridyl)-1,3-propanedione (DPPD). HPLC analysis of these derivatives achieved sub-femto mole levels of detection [106]. Another recent study reported a new improved label, RapiFluorMS (RFMS), which enables rapid labeling of N-glycans, released as glycosylamine, at their reducing end immediately after PNGase F treatment.…”
Section: Step-by-step Description Of Workflowsmentioning
confidence: 99%
“…90 Some of the most commonly used fluorescence reagents for glycan analysis include 2-aminobenzamide (2-AB), anthranilic acid (2-AA) 2-aminopyridine (2-AP), and 1-phenyl-3-methyl-5-pyrazolone (PMP). 90 2-AA-labeled glycans are most often detected with fluorescence, but some reports analyze 2-AA labeled N -glycans with reverse phase LC–MS.…”
Section: Derivatization Of Glycansmentioning
confidence: 99%
“…90 Some of the most commonly used fluorescence reagents for glycan analysis include 2-aminobenzamide (2-AB), anthranilic acid (2-AA) 2-aminopyridine (2-AP), and 1-phenyl-3-methyl-5-pyrazolone (PMP). 90 2-AA-labeled glycans are most often detected with fluorescence, but some reports analyze 2-AA labeled N -glycans with reverse phase LC–MS. 91 Whereas the previously reported literature indicates negligible desialylation during 2-AB labeling of N-linked glycans, a recent report indicates that there is some loss of sialic acid from highly sialylated glycans during 2-AB derivatization or possibly other reductive amination procedures as well.…”
Section: Derivatization Of Glycansmentioning
confidence: 99%